Pengaruh Gender, Tekanan Ketaatan, Kompleksitas Tugas dan Pengalaman Auditor terhadap Audit Judgment - Reni Yendrawati; Anita Sulistia Ragil (Jurnal Aplikasi Bisnis, 2017)
This study aims to examine the influence of gender, compliance pressure, task complexity and experience of the audit judgment. The research was conducted in Denpasar by using 57 public accountants as respondents. Convenience sampling was chosen in the process of collecting data.The research proved that gender did not significantly affect the audit judgment, while the obedience pressure, task complexity have negative affect. Experience has significant and positive impact on audit judgment.